Study on coordinated allocation of conventional and unconventional water resources in typical regions of North China - Chai, Qihui; Han, Wenhao; Wan, Fang; Ding, Zelin; Wu, Feng (Frontiers in Earth Science, 2023)
North China Plain is an important production base of grain, cotton and fruits in China. But the climate is dry and rainless, water resources are scarce. The combination of water resources, population and cultivated land is extremely unbalanced, making the region a serious water shortage area in China. In addition to long-term groundwater over-exploitation, water shortage has become an important bottleneck restricting the economic and social development of the North China Plain and national food security. Therefore, making full use of unconventional water resources and reducing the proportion of conventional water resources will alleviate the shortage of water resources and improve the utilization of water resources. Taking Hengshui City as an example, this paper establishes an optimal allocation model of water resources with the minimum relative water shortage rate as the objective function, the coordinated allocation of water resources between conventional water and unconventional water is studied, and various available water sources are effectively allocated between regions and water use departments. The genetic algorithm is used to solve the model, with 2020 as the current year, and optimize the allocation of water resources in Hengshui City in 2020 and 2025. The results show that the water demand of each county in Hengshui City is guaranteed in 2025, and there is no water shortage. In the 2025 level year, the total amount of unconventional water resources in Hengshui City increased compared with that in 2020, with an increase of 21.9144 million m³. Among them, the increase of brackish water consumption is 11.3244 million m³, and the increase of sewage reuse water consumption is 10.59 million m³, which effectively alleviates the contradiction between supply and demand of water resources in Hengshui City.